HUBUNGAN ANTARA FLEKSIBILITAS SENDI BAHU DAN POWER OTOT LENGAN DENGAN KECEPATAN SMASH DALAM OLAHRAGA BULUTANGKIS - Mi'rajul Taufik; Andi Gilang Permadi; Kurnia Taufik (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2017)
Background of badminton playing ability at 10-year-old athlete O2SN athletes is very important, especially in achieving badminton achievement. The problem that arose in this research is the relationship between flexibility of shoulder joint and arm muscle power with smash speed in badminton sport. Badminton is one of the most popular sports, attracting different age groups, different skill levels for both men and women. Badminton games will be more interesting where the teacher / trainer creative in the development of the forms of teaching. The formulation of the problem in this research with the title "The relationship between shoulder joint flexibility and arm muscle power with smash speed in badminton sport athlete athlete O2SN age 10-12 years 2 Buwun Mas Subdistrict Sekotong District West Lombok Year 2017" with aim to know whether there is Relationship between flexibility of shoulder joint and arm muscle power with smash speed in badminton sport of athlete athlete O2SN age 10-12 year 2nd class Buwun Mas Subdistrict Sekotong West Lombok Regency Year 2017. The design used in this research is "Quantitative". The determination of research subjects using "Study population" with the subject of research as many as 15 athlete beginners O2SN aged 10-12 years 2 Buwun Mas group that used as research samples. Data collection methods used to obtain research data using the method of action test and documentation method, while the method to analyze the data using the method of double correlation statistics with the formula F-count which will then be compared with the F-table. From the research results can be seen F-test is the value of F-hitung obtained value of 0.74. Then the value of F-table with degrees of freedom F (1 - a) [(db - 2), (db = 15 - 2 - 1 = 12). To be able to reject the null hypothesis (ho) required F-count value equal to or greater than F-table value and at a significant level of 5% indicates a value of 3.885.This means that 0.74 <3.885 or in other words the value of F-arithmet obtained is smaller than the limit number of rejection of nil hypothesis (ho) listed in F- Based on the results of this study it can be concluded that: "No Relation Between Flexibility of Shoulder Joint and Power Sleeve Arm With Smash Speed In Sports Badminton Athletes O2SN Beginners Age 10-12 Years 2nd Class Buwun Mas Sub District Sekotong West Lombok Year 2017